Migration law for random parameters rockfall in steeply dipping coal seams - Liu, Ming; Chen, Jie; Xiao, Yang; Lv, Wenyu (Frontiers in Earth Science, 2023)
The migration process of rockfall has certain complexity and randomness in steeply dipping coal seams (SDCS). The three-dimensional random migration of rockfall with random parameters cannot be accurately simulated. Taking the transport process of arbitrarily shaped rockfall formed by roof leakage in steep seam working face as the research object, a method for generating rockfall with the random shape of irregular polyhedrons based on the ellipsoid equation is provided. And based on the geographic information system data, such as the contour line of the bottom floor of the working face, the 3D grid model of the bottom floor is established. The random transport process of rockfall in three-dimensional mining space was simulated using Monte Carlo random simulation technology combined with the energy tracking method (ETM) to compile the program, considering the randomness of collision recovery coefficient and friction coefficient between rockfall and working face floor. The influence of randomness of parameters on the migration velocity, angular velocity and energy of rockfall is analyzed. With the increase of the coefficient of variation of parameters, the influence of the randomness of the parameters on the transport characteristics of rockfall becomes greater. The impact of the collision recovery coefficient on the migration process of rockfall is much more significant than that of the friction coefficient. The offset ratio of rockfall increases with the increase of the variation coefficient. The method presented in this paper can be used to simulate the motion of rockfall more accurately, and a theoretical basis is provided for predicting and protecting rockfall hazards.